2014
DOI: 10.1002/jbm.b.33273
|View full text |Cite
|
Sign up to set email alerts
|

Control of Ag nanoparticle distribution influencing bioactive and antibacterial properties of Ag-doped mesoporous bioactive glass particles prepared by spray pyrolysis

Abstract: Mesoporous bioactive glasses (MBGs) have become important bone implant materials because of their high specific surface area resulting in high bioactivity. Doping MBGs with Ag removes one of the remaining challenges to their applications, namely their lack of intrinsic antibacterial properties. In present work we demonstrate that Ag-doped MBGs can be prepared in one-step spray pyrolysis (SP) process. The SP preparation method offers the advantages of short processing times and continuous production over the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…The mesoporous structure of the synthesized MBG could be determined by its IV N 2 adsorption and desorption isotherm curve with a H1-type hysteresis loop at high relative pressure according to the IUPAC classification. 11,43 The present study is supported by previous investigations showing the same type of hysteresis loop in the N 2 isotherms for mesoporous materials, 12,14,45,46 however in this study the organization and arrangement of the mesopores were not confirmed (e.g., by TEM). In addition, previous studies developing MBGs have shown higher surface area, pore volume, and pore diameter that should enhance the MBG capability to incorporate therapeutic agents and to achieve a higher HCAp formation to bond to bone.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The mesoporous structure of the synthesized MBG could be determined by its IV N 2 adsorption and desorption isotherm curve with a H1-type hysteresis loop at high relative pressure according to the IUPAC classification. 11,43 The present study is supported by previous investigations showing the same type of hysteresis loop in the N 2 isotherms for mesoporous materials, 12,14,45,46 however in this study the organization and arrangement of the mesopores were not confirmed (e.g., by TEM). In addition, previous studies developing MBGs have shown higher surface area, pore volume, and pore diameter that should enhance the MBG capability to incorporate therapeutic agents and to achieve a higher HCAp formation to bond to bone.…”
Section: Discussionsupporting
confidence: 85%
“…BGs have been modified over the years with the incorporation of diverse antibacterial and antibiofilm agents to counteract bone infection. Various studies have reported the incorporation of metal oxides, antibiotics and other organic agents into BGs; however, there is no consensus until present day concerning which antibiofilm agent is the most effective for bone infection treatment . Indeed BG of “S53P4” composition is commercially available as an effective agent to counteract osteomyelitis conditions .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This bond capability gives bioactive glass a wide range of biomedical applications [1]. Many researchers are working to enhance this material bioactivity and to develop many more aspects such as its antibacterial properties also and its cytotoxicity [2][3][4]. The researchers have focused their attention on bioglass ceramics which are formed through sol-gel synthesis and have SiO 2, CaO and P 2 O 5 as major components.…”
Section: Introductionmentioning
confidence: 99%
“…Ordered metal based microstructures can find potential applications in bioactive materials [16], structures with plasmonic properties [17], materials with magneto and piezo resistivity [18], surfaces with shape-memory [19] and catalytic materials [20].…”
Section: Resultsmentioning
confidence: 99%